Environmental Ethics in the Spiritual Perspective of Hinduism, Buddhism, and Islam: Aligning Roles and Finding Intersecting Paths - Pratama Yudha Pradheksa; Didid Haryadi; Abu Samsudin; Karunia Hazyimara (Pustaka Peradaban, 2023)
This article aims to examine the views of Hindu and Buddhist spiritualism related to efforts to deal with environmental damage in Indonesia and try to find common ground between Hindu and Buddhist spiritualism regarding environmental preservation with the teachings of Sufism in Islam. The method used in this article is library research with a descriptive-qualitative approach. The research shows that the ecological damage that has occurred in Indonesia is very worrying. This happens because humans have no concern for their environment, they only focus on taking the maximum benefit for profit alone. Religion has authority in environmental preservation by instilling ethics and morals in humans. Spirituality in Hinduism, Buddhism, and Islam is aimed at getting closer to God. There is a concept for each religion to increase one's spirituality, namely through bhakti marga yoga in Hinduism, hasta ariya magha in Buddhism, and Sufism in Islamic teachings. The concepts shared by each of these religions have in common to shape one's spirituality which can be reflected in a moral person. Immoral cases such as environmental damage are a big thing that can be solved by increasing one's spirituality.